2009
DOI: 10.1016/j.jss.2009.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Adrenal Cortical Progenitor Cells Enriched by Nile Red

Abstract: Background The adrenal cortex may contain progenitor cells useful for tissue regeneration. Currently there are no established methods to isolate these cells. Material and Methods Murine adrenal cells were sorted into a Nile-Red-bright (NRbright) and a Nile-Red-dim (NRdim) population of cells according to their degree of cholesterol content revealed by Nile Red fluorescence. The cells were transplanted under the renal capsule to determine their ability for regeneration. Results The NRbright cells contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…However, the expression of zonal-specific genes, Cyp11b1 and Cyp11b2, were substantially suppressed for the cells collected from the outermost outlets, indicating that those cells were least differentiated (P<0.05). Collectively, the results show that more differentiated multicellular clusters of adrenal cells, expressing higher levels of zonal-specific genes (Cyp11b1 and Cyp11b2) were enriched at inner outlets (outlet 2 and 3), while the expression levels of those genes were significantly lower for the adrenal cortical progenitor cells collected at the outermost outlets (outlet 1) [25]. The clear differences in gene expression profiles of cells collected at different outlets suggest that differences in differentiation of adrenal cortical cells can be reflected in biophysical property dissimilarities (e.g., adhesive properties and relative tendency to remain in clusters after tissue dissociation).…”
Section: Resultsmentioning
confidence: 81%
“…However, the expression of zonal-specific genes, Cyp11b1 and Cyp11b2, were substantially suppressed for the cells collected from the outermost outlets, indicating that those cells were least differentiated (P<0.05). Collectively, the results show that more differentiated multicellular clusters of adrenal cells, expressing higher levels of zonal-specific genes (Cyp11b1 and Cyp11b2) were enriched at inner outlets (outlet 2 and 3), while the expression levels of those genes were significantly lower for the adrenal cortical progenitor cells collected at the outermost outlets (outlet 1) [25]. The clear differences in gene expression profiles of cells collected at different outlets suggest that differences in differentiation of adrenal cortical cells can be reflected in biophysical property dissimilarities (e.g., adhesive properties and relative tendency to remain in clusters after tissue dissociation).…”
Section: Resultsmentioning
confidence: 81%
“…The technique of adrenal cell transplantation in mice was described previously; 5,11 however, it had not been demonstrated that these cells could restore the adrenal function. In addition to improved survival, mice that received a sufficient dose of adrenal cells also had near normal levels of corticosterone 14 days after staged bilateral adrenalectomy.…”
Section: Discussionmentioning
confidence: 99%
“…After removing the surrounding fat, they were incubated in the digestion mixture at 37°C for 1 hour with gentle shaking. 11 The digestion mixture consisted of 10 mL of HBSS containing 2 mg/mL collagenase I, 0.05 mg/mL DNase I, and 5 mg/mL bovine serum albumin. After dispersing the cells through a pipette, they were washed with Adrenal Media and were filtered through a 70-μm strainer (Millipore, Bedford, MA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering these drawbacks related to adrenal hormone supplementation, several alternative therapeutic approaches have been proposed and tested. 129 These include auto-and allotransplantations of the adrenal glands, 130 adenoviral-associated virus (AAV)-mediated gene targeting, 131,132 and either allo-or xenotransplan-tation of adrenocortical cells, [133][134][135][136][137][138][139] or various stem cells reprogrammed into steroidogenic-like cells. [140][141][142] Apart from allotransplantation of a whole human adrenal with its intact microenvironment, all the other experiments were performed in animals, preferentially using rodent models.…”
Section: Therapeutic Approaches To Restore Adrenal Gland Functionmentioning
confidence: 99%